Dataset: Global Trends in Digital Forensics and Fingerprint Research: A Comprehensive Analysis - Aulia Sarah Azizah; Mochammad Tanzil Multazam (International Consortium of Education and Culture Research Studies, 2022)
The purpose of retrieving this data is to determine the number of journal articles related to digital forensics and fingerprinting. Through lens.org analysis with appropriate keywords and filters, 133 relevant documents were found. The study revealed that the University of Lausanne is the most active institution in this field, with the most research in 2019. The most explored fields of study include forensic science and computer security. The most active countries in this research were the UK, the US, and Switzerland. These results suggest that this data can serve as a quick guide to further research and development methods, such as forensic 3D modelling and photogrammetry. In addition, this data is useful for authors, readers, and researchers interested in the topic of digital forensics and fingerprinting.Highlights: Dominant institutions and countries: University of Lausanne leads the research, with the United Kingdom, United States, and Switzerland as the most active countries. Peak research activity: The highest number of journal articles published in 2019, focusing on various aspects of digital forensics and fingerprinting. Interdisciplinary exploration: Research spans across forensic sciences, computer security, and law, indicating diverse applications and implications of digital forensics and fingerprinting techniques.